IDEOLOGEMI OF MODERN CONCEPTUALLY METHODOLOGICAL “UPDATE” IN ECONOMIC THEORY - V. Mandubura (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2013)
The causes and theoretical definition of modern economic ideologemes are examined in the article. The peculiarities of origin and current forms of social and economic orders implemented with help of economic theory are disclosed. Author’s vision of directions in conceptual and methodological renewal of economic theory in modern terms is given.